Grape and Wine Biotechnology 2016
DOI: 10.5772/64873
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis-Related Proteins in Grape

Abstract: An overview of major pathogens and their control, plant defense mechanisms, and pathogenesis-related PR proteins and their roles in pathogen control is presented herein. Vitis vinifera, including wine grape and table grape, is one of the most valuable horticultural crops in the world because of its commercial use. However, V. vinifera cultivars are extremely susceptible to pathogens, particularly fungi and oomycetes, such as Botrytis cinerea and Plasmopara viticola, respectively. Plants have various defense me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 69 publications
2
10
0
Order By: Relevance
“…Often PR proteins are highly expressed during osmotic stress conditions. In accordance with our results, PR proteins are reported to be highly expressed during the somatic embryo development of various species like Vitis vinifera 30 , Vitis pseudoreticulata 31 , Cichorium 29 and Pinus nigra Arn. 32 .…”
Section: Discussionsupporting
confidence: 92%
“…Often PR proteins are highly expressed during osmotic stress conditions. In accordance with our results, PR proteins are reported to be highly expressed during the somatic embryo development of various species like Vitis vinifera 30 , Vitis pseudoreticulata 31 , Cichorium 29 and Pinus nigra Arn. 32 .…”
Section: Discussionsupporting
confidence: 92%
“…The expression level of genes encoding PR‐2 (β‐1,3‐glucanases), PR‐3 (chitinases), PR‐5 (thaumatin‐like proteins) and the PR‐protein 10.3 were increased upon the treatment with B. bassiana within 24 h after treatment. These results confirm previous reports that these genes are involved in the defence response of grapevines to infestation with pathogens (Kortekamp, ; Fung et al , ; Albertazzi et al , ; Adrian et al , ; Enoki & Suzuki, ) and are also related in response to colonization by biotrophic fungi (Perazzolli et al , ). In addition, other defence‐related genes like those associated to the stilbene synthesis and related genes were found to be up‐regulated.…”
Section: Discussionsupporting
confidence: 92%
“…According to molecular structure and enzyme activity, 17 families of PR proteins have been reported, some of which possess antimicrobial activity. Among them, PR‐1 (antifungal), PR‐2 (β‐1,3‐glucanase), PR‐3 and PR‐4 (chitinase), PR‐5 (thaumatin‐like protein), PR‐10 (ribonuclease), PR‐14 (lipid transfer protein), PR‐15 (oxalate oxidase), and PR‐16 (oxalate oxidase like protein) have been detected in grapevine (Enoki and Suzuki, 2016). Several research studies have demonstrated that these PR proteins are strongly induced in grapevine by fungal plant pathogens (Jacobs et al , 1999; Jayasankar et al , 2003; Godfrey et al , 2007; He et al , 2013).…”
Section: Introductionmentioning
confidence: 99%